Incidence of Job Advert on Manpower Resourcing in the Public Sector: Perspective of Nigerian Maritime Administration and Safety Agency - Edih, University Ovuokeroye; Dbright , Okiemute Agboro; Faghawari, Nyanayon David (Polytechnica, 2022)
The study examined the incidence of job advert on manpower resourcing in the public sector, perspective of Nigerian Maritime Administration and Safety Agency. The objective of the study is to evaluate the effect of job advert on manpower resourcing in public organization. Data were collected through structured questionnaire administered to 350 sample population. Correlation and multiple regressions analyses were used to analyse the relationships among variables and test the hypothesis respectively. The study revealed that job advert has a positive and significant effect on manpower resourcing in Nigerian Maritime Administration and Safety Agency. It thus concludes that job adverts through television, radio, newspapers, persons-to-persons and the internet channels affect manpower resourcing and employee's performance. The study recommends that organizations should develop a job advert communication model that identifies and attracts pool of applicants to apply for the vacant jobs since it leads to high recruitment intensity and the employment of capable and experienced manpower.